Paradoxical Connections in Sarah Ruhl’s Dead Man’s Cell Phone: Sociological Study - Muhammed, Ahmed A. (KOYA UNIVERSITY JOURNAL OF HUMANITIES AND SOCIAL SCIENCES, 2023)
The paper examines different types of paradoxical connections in Sarah Ruhl’s Dead Man’s Cell Phone with respect to contemporary characteristics of American theatre. It is so clear that the play has a smooth transformation or connection between paradoxical states or situations. The transformation happens due to spatial, and temporal conditions, and different humankind values. The play is full of different types of connections due to social ties, contradictive life situations, death and life, the whole and the parts, the spatial and the temporal transformation, truth and lies, happiness and misfortune, fancy and facts, and humanity with technology. The study is qualitative depending on the study of the cases within the play that are contradicting each other, yet they serve in deepening the meaning and the understanding of the cases. The paradoxical issues to be studied in a comparative way, these comparative situations serve higher thematic issues in a philosophical dimension in very carefully woven relations between the characters and situational environment as well. The common sense that the play made is to accept the philosophy of black and white as positive paradoxical relation, that the black helps to see the pure white and vice versa. Common unanswered questions are to be presented in a rhetorical and philosophical manner; targeting these questions is the way of being closer to a bunch of truths about the complicated fabric relationships which link the characters all together.